Production and detoxification of H₂O₂ in lettuce plants exposed to selenium - Ríos, J.J; Blasco, B; Cervilla, L.M; Rosales, M.A; Sanchez-Rodriguez, E; Romero, L; Ruiz, J.M (Annals of applied biology, 2009)
Selenium is considered an essential element for animals. Despite that it has not been demonstrated to be essential for higher plants, it has been attributed with a protective role against reactive oxygen species in plants subjected to stress. In this study, lettuce plants (Lactuca sativa cv. Philipus) received different application rates (5, 10, 20, 40, 60, 80 and 120 μM) of selenite or selenate, with the aim of testing the effect of Se on the production and detoxification of H₂O₂ in non-stressed plants. The results indicate that the form selenate is less toxic than selenite; that is, the plants tolerated and responded positively to this element, and even increasing in growth up to a rate of 40 μM for the form selenate. On the contrary, the application of selenite triggered a higher foliar concentration of H₂O₂ and a higher induction of lipid peroxidation [malondialdehyde content and lipoxygenase activity] in comparison to that observed after the selenate application. Also, the plants treated with selenate induced higher increases in enzymes that detoxify H₂O₂, especially ascorbate peroxidase and glutathione (GSH) peroxidase, as well as an increase in the foliar concentration of antioxidant compounds such as ascorbate and GSH. These data indicate that an application of selenate at low rates can be used to prevent the induction in plants of the antioxidant system, thereby improving stress resistance.